Novel molecular mechanisms involved in hormonal regulation of lactate production in Sertoli cells - Regueira, Mariana (2015)
The aim of the study was to analyze molecular mechanisms involved in follicle-stimulating hormone (FSH) and basic Fibroblast Growth Factor (bFGF) regulation of lactate production in rat Sertoli cells. The regulation of pyruvate availability, which is converted to lactate, could be a mechanism utilized by hormones to ensure lactate supply to germ cells. On one hand, the regulation of 6-phosphofructo-2-kinase/fructose-2,6-biphosphatase (PFKFB) expression could result in increased glycolysis, while an increase in pyruvate availability may also result from a lower conversion to acetyl-CoA by negative regulation of pyruvate dehydrogenase complex (PDC) activity by phosphorylation. Sertoli cells cultures obtained from 20-day-old rats were used. Stimulation of the cultures with FSH or bFGF showed that FSH increases Pfkfb1 and Pfkfb3 expression while bFGF increases Pfkfb1 mRNA levels. Additionally, we observed that FSH-stimulated lactate production was inhibited in the presence of a PFKFB3 inhibitor, revealing the physiological relevance of this mechanism. As for the regulation of PDC, analysis of pyruvate dehydrogenase kinase (Pdk) expression showed that FSH increases Pdk3 and decreases Pdk4 mRNA levels while bFGF increases the expression of all Pdks. In addition, we showed that bFGF increases phosphorylated PDC levels and that bFGF stimulated lactate production is partially inhibited in the presence of a PDK inhibitor. Altogether, these results add new information regarding novel molecular mechanisms involved in hormonal regulation of lactate production in Sertoli cells. Considering that lactate is essential for the production of energy in spermatocytes and spermatids, these mechanisms might be relevant in maintaining spermatogenesis and male fertility.